Human Concern: An Overview on Attention of Mahua Literature towards May Fourth through Early Chinese Newspapers （“人”的关怀：从新马早期报章看马华文坛对“五四”之关注 ）） - é»„ä½©æ™¶, Wong Pei Tjin (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2015)
Abstract The beginning of Mahua literature is closely related with the May Fourth literature. During mid-19th century, some of the Chinese migrated to Southeast Asia (the Nanyang) due to war, famine and economic issues. The Chinese immigrants not only paid close attention to the land that they currently stayed but also to their homeland as well. Thus, newspapers had been launched to spread the patriotism among the Chinese immigrants. Newspapers are playing an important role to "improve the condition of society, advocate new culture and instil the feeling of patriotism in the immigrants". Therefore, the notions of literary creation and literature works can be published on the newspapers and their respective supplementary copy. Among the discussions, 'human' which is one of the hottest topics during the May Fourth era, is also known as one of the important component of the early Chinese newspaper of Mahua. This paper will discuss on the attentions given by the Mahua literature to the literature and ideology trends of May Fourth, especially the introduction on "human" and humanism through Sin Kuo Min JitPoh and YikKuan Poh. 摘要 马华文学的萌芽与“五四”文坛的关系极为密切。自19世纪中叶开始，部分中国 人民就因战事、饥荒、经济等问题而陆续迁移至南洋一带。虽身处异乡，但南迁 而来的人民时刻关注中国国内与侨居地的动态。他们便透过创办报章以起到“改 良社会、提倡新文化、灌输侨民爱国思想”的作用凸透过这些报章与副刊，马华 文坛对文艺创作所提出的相关主张、文学创作等也得以发表，进而形成了一个重 要的马华文学论述场域凸当中，在“五四”时期备受热议的有关“人”的课题亦 在马华早期报章上占了一定的分量。因此，本文将尝试透过《新国民日报》与 《益群报》这一文学论述场域，探析马华早期文坛对中国“五四”文艺与思潮， 尤其是对“人”之关注与人道主义的引介。